The Athlete's Wrist: Ulnar-Sided Pain - Yamabe, Eiko; Nakamura, Toshiyasu; Pham, Peter; Yoshioka, Hiroshi (Seminars in Musculoskeletal Radiology, 2012)
Ulnar-sided wrist pain is one of the most common symptoms in athletes of baseball, racket sports, golf, and wrestling where there is frequent use of the hands as well as in soccer and running, where hand use is minimal. Compared with all wrist injuries, ulnar-sided wrist injury is a relatively serious condition for athletes because it plays an important role in performing a strong grip and in the rotation of the forearm.Ulnar-sided wrist pain in athletes can be related to acute trauma or chronic overuse. Acute trauma can lead to bone fractures and sprains/tears of ligaments. Repetitive mechanical stresses to tendons, ligaments, and the joint structures can lead to tendinitis or osteoarthrosis.Diagnosis of the ulnar-sided wrist pain is challenging both for hand surgeons and radiologists because of the small and complex anatomy. In the present article, we discuss mechanisms of wrist injury, sports-specific ulnar-sided wrist injuries, and the differential diagnosis of ulnar-sided wrist pain.
Keywords: athlete; sports; ulnar-sided wrist pain; MRI; radiograph